Anthropogenic influence on summer precipitation trends over South America in CMIP5 models - Vera, Carolina Susana (2015)
Austral summer rainfall trends are analysed over South America from observations and simulations of the Coupled Model Intercomparison Project version 5 between 1902 and 2005. Positive trends in southeastern South America (SESA) and negative ones in the southern Andes (SAn) are the most significant observed features. Mean trends obtained from an ensemble of 59 simulations from 14 models for the historical experiment (including both natural and anthropogenic forcings) are able to reproduce those precipitation changes, although weaker than observed. Most of the simulations reproduce the right sign of the precipitation changes at both regions. However, associated uncertainty ranges (due to both inter-model dispersion and internal climate variability) are still large. Mean trends for the historical experiment are statistically distinguishable from those obtained for the natural-forcing-only experiment, which exhibit negligible mean values at both regions. Results allow concluding that the anthropogenic forcing has at least a partial contribution in explaining the precipitation changes observed in both SESA and SAn regions during the last century.